Pengharaman â€œKhamarâ€ Dalam Al-Qurâ€™an (Aplikasi Semiotika Charles Sanders Peirce) - Muhammad Romadhon (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2024)
In this paper, Charles Sanders Peirce's semiotic hypothesis is utilized, in particular triad (representamen, object and interpretant) to uncover the stages in regards to the denial of Khamar in the Qur'an as a sign. The strategy for this examination is subjective substance investigation, to be specific exploration that means to distinguish the message of a media as an object of examination. From this examination, it very well may be inferred that the refrains of the Qur'an which talk about the law with respect to khamr are surely completed bit by bit until they are prohibited on the grounds that considering the mischief and advantages of intoxicants are fortified by the translation and Asbabunnuzul of the section. Research like this absolutely should be created to grow the investigation of the Qur'an and the legitimacy of the Qur'an in different spaces and times. Keyword: Al-Qurâ€™an, Khamar, Semiotika.